Investigating the effect of geopolitical risk on defense companies’ stock returns - Catalin Gheorghe; Oana Panazan (Heliyon)
This study examines the influence of geopolitical risk (GPR) on the stock returns of 75 global representative defense companies. Our argument is based on the premise that the Crimean Peninsula's 2014 annexation was a turning point for the defense industry. The study uses wavelet coherence and phase differences to examine daily datasets spanning from January 1, 2014 to December 31, 2023. We find that 50.6 % of the defense companies experienced immediate effects following the Crimean Peninsula's annexation. Among all headquarters, the reaction of companies from Europe, the US, and South Korea in 2014 was noteworthy. Subsequently, during the COVID-19 pandemic, 30.6 % of companies recorded movements with a medium frequency, revealing negative and moderate influence. Furthermore, the Russia–Ukraine war impacted the stocks of 81.4 % of the defense companies in our sample. The results clearly demonstrate the defense industry's global growth trend, particularly after 2014. Additionally, the conflict between Israel and Hamas that began in October 2023 has had a local effect on the Israeli defense industry without contributing to the spread of GPR. The study concludes that investors and decision makers must shift orientation toward knowledge of defense industry stocks to hedge and diversify the risks induced by GPR.